Cyber security awareness in using digital platforms among students in a higher learning institution / Rajeswari Raju, Nur Hidayah Abd Rahman and Atif Ahmad - Raju, Rajeswari; Abd Rahman, Nur Hidayah; Ahmad, Atif (Universiti Teknologi MARA, 2022)
As COVID-19 took hold, online learning became the norm as universities and classrooms worldwide were forced to close their doors. Education institute closures impacted more than 1.2 billion students across 186 countries as of April 2020. This pandemic, too, has shifted our Malaysian education sector as well. Academicians and students are adopting online learning via open and distance learning platforms. Education 5.0 is the revolution of human intelligence and cognitive computing. When the world is moving towards this, the major challenge one will face is the challenges in this digitalisation era, the challenges on cyber security and the risk associated with it. This study uses a digital learning platform to examine the cyber security awareness among UiTM Terengganu Faculty of Computer and Mathematical Sciences students. The study is significant to focus on the weakness and to educate the students about being cyber victims. The data was collected using a set of questionnaires among 110 students. Numbers and statistics from open-ended and closed-ended questions helped obtain data. Descriptive analysis shows that many students have awareness and knowledge of cyber security, cyberattack, and cyberbullying.